2019
DOI: 10.3389/fmicb.2019.01549
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Densovirus Isolated From the Asian Tiger Mosquito Displays Varied Pathogenicity Depending on Its Host Species

Abstract: Mosquito-borne viral diseases (MBVDs) continue to pose a significant global public health burden. Mosquito control remains a core intervention strategy in integrated mosquito management (IMM) programs to reduce the transmission of MBVDs. Mosquito densoviruses (MDVs) are mosquito-specific entomopathogenic viruses, and their attractive biological and pathogenic characteristics make MDVs potential biological control agents as alternatives to traditional chemical pesticides. However, different viral strains vary g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 77 publications
0
26
0
Order By: Relevance
“…aegypti and Ae. albopictus first instar larvae significantly decreased pupation and emergence rates 33 . However, the diversity of experimental designs used does not allow easy comparison of the results across studies, due to differences in infection methods, environmental conditions, viral titers, and stage of larvae infected.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…aegypti and Ae. albopictus first instar larvae significantly decreased pupation and emergence rates 33 . However, the diversity of experimental designs used does not allow easy comparison of the results across studies, due to differences in infection methods, environmental conditions, viral titers, and stage of larvae infected.…”
Section: Discussionmentioning
confidence: 95%
“…Adult mortality has not been evaluated in this work, but many studies have shown that DVs infection of mosquito larvae affects the life traits of infected adults 33 , 34 , 37 . Thus, the effects of sublethal infection of Ae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Culex pipiens densovirus (CpDV) is an insect‐specific densovirus ( Parvoviridae ) that has been isolated following high mortality in laboratory colonies of C. pipiens (Jousset, Baquerizo, & Bergoin, 2000). However, high mortality has not been shown through experimental infections, and persistently infected C. pipiens colonies do not exhibit apparently high mortality, in contrast to what has been observed for other mosquito densoviruses (Altinli, Soms, et al, 2019; Jousset et al., 2000; Li et al., 2019). Recently, CpDV has been found to be widespread in C. pipiens ( sensu lato [ s.l .])…”
Section: Introductionmentioning
confidence: 90%